Implementasi Transaksi Non-Tunai Sebagai Dasar Tata Kelola Pemerintah Yang Baik: Studi Kasus pada Pemerintah Kabupaten Jombang - Suluh Hendrawan; Nur Anisah; Lina Nasihatun Nafidah (Department of Accounting-Faculty of Economic and Business (FEB), 2019)
The implementation of non-cash transactions in local governments is the government's step in the struggle for the public interest. This study discusses how to implement non-cash transactions in local government in an effort to realize good governance. With qualitative case studies obtained, the data in this study were collected by in-depth interviews. The results of this study prove that accountability, approval and administrative order have been successfully completed in the implementation of non-cash transactions. However, the efficiency of the use of the budget has not been able to optimize. Besides that, at the level of strategy, the system and structure are already running well. Factors of ability, human resources and leadership style that need to be considered in order to be successful in supporting good governance management strategies.